Gut microbiota and metabolite features in NSCLC nude mouse models of subcutaneous tumor and leptomeningeal metastasis: a microbiome-metabolome combined analysis - Du, Yang; Fan, Chengjuan; Song, Xiaowei; Teng, Chong; Zhang, Zhichao; Zhang, Jing; Zhao, Tianjiao; Xin, Tao (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe incidence and mortality rates of lung cancer are both elevated. In lung cancer, leptomeningeal metastasis (LM) is a serious consequence. Patients suffering from LM have severe symptoms and a short survival time. Numerous studies have shown a connection between the prognosis of lung cancer and the composition of the gut microbiota. However, Current knowledge regarding the gut microbiota and metabolites in lung cancer patients with LM, as well as their potential impacts on LM pathogenesis, remains remarkably limited.MethodWe established a mouse model of LM from lung cancer and a subcutaneous metastatic model, using wild-type mice as controls. Each of the three groups above contained six mice. We examined the fecal microbiota and metabolites of three groups of mice utilizing 16S rRNA gene sequencing and liquid chromatography-mass spectrometry (LC-MS) technologies. Conducting correlation analysis on microbiome and metabolome data concurrently to identify significant relationships.ResultMice with LM had a different gut microbiota and metabolite composition than wild-type and subcutaneous metastatic mice; the LM group had a higher ratio of Firmicutes to Bacteroidetes. Differential metabolites are primarily seen in pathways such as Nicotinate and nicotinamide metabolism, Tryptophan metabolism; Association analysis reveals that some changes in gut microbiota are linked to metabolites, such as a positive association between Eubacteria and N-Acetylsorotonin.ConclusionSome microbiota and metabolites may act as biomarkers for LM, controlling gut microbiota and metabolites or giving a novel option for research into lung cancer leptomeningeal metastases.